The functional connectivity in the motor loop of human basal ganglia. - Rodriguez-Sabate, Clara; Sabate, Magdalena; Llanos, Catalina; Morales, Ingrid; Sanchez, Alberto; Rodriguez, Manuel (Brain Imaging & Behavior, 2017)
Basal ganglia interact in a complex way which is still not completely understood. The model generally used to explain basal ganglia interactions is based on experimental data in animals, but its validation in humans has been hampered by methodological restrictions. The time-relationship (partial correlation) of the fluctuations of the blood-oxygen-level-dependent signals recorded in the main basal ganglia was used here (32 healthy volunteers; 18-72 years of age; 16 males and 16 females) to test whether the interaction of the main basal ganglia in humans follows the pattern of functional connectivity in animals. Data showed that most basal ganglia have a functional connectivity which is compatible with that of the established closed-loop model. The strength of the connectivity of some basal ganglia changed with finger motion, suggesting that the functional interactions between basal ganglia are quickly restructured by the motor tasks. The present study with the motor cortico-BG loop centers supports the circling dynamic of the basal ganglia model in humans, showing that motor tasks may change the functional connectivity of these centers.